Corporate Prosecution in Criminal Acts of Corruption: Opportunity and Challenge - Muhammad Sofyan, Andi (Jurnal Mulawarman Law Review, 2019)
The corporation as an entity or legal subject whose existence contributes greatly in promoting economic growth and national development. However in reality, it is often for corporations to commit various criminal acts (corporate crime) that have a detrimental impact on the state and people. This research is normative legal research. Legal research which places the law as a normative system. The research approach uses a statutory approach and a conceptual approach. The results showed that the enactment of the Supreme Court Regulation No. 13 Year 2016 was to clarify the guidelines for the Public Prosecutor in prosecuting corporate defendants in corruption criminal acts. The application of sanctions against corporations as perpetrators of corruption is carried out as an effort to recover the losses of the State and the restoration of the state’s economy is an appropriate step considering the essence of criminal punishment in eradicating criminal acts of corruption aimed at recovering state losses or the state’s economy.